HUBUNGAN SOSIAL EKONOMI KELUARGA DENGAN PRAKTIK PEMBERIAN MAKANAN PENDAMPING ASI PADA BAYI USIA 6-12 BULAN : RELATIONS OF SOCIO-ECONOMIC WITH THE PRACTICE OF GIVING COMPLETE FOODS FOR BABIES AGE 6-12 MONTHS - Stianto, Mitayakuna; Lianawati, Feni; Rahayu, Yustina (WELL BEING, 2021)
Introduction: Complementary breast milk food (MPASI) is food given to babies aged 6-24 months in addition to breast milk starting from food with a liquid consistency until it gradually becomes solid and takes place in stages. Giving MP-ASI incorrectly will risk the baby becoming malnourished. This study aims to determine the socio-economic relationship between mothers and the practice of providing complementary breast milk to babies aged 6-12 months. Method: This research is an observational analytical research, cross sectional study design. The population in this study were mothers who had babies aged 6-12 months in the Tembelang Community Health Center area, Jombang Regency. The technique used to determine the sample in this research used incidental sampling with a total of 55 respondents. Data collection using a questionnaire. Results: Data analysis using the Spearman rank test showed that there was no significant relationship between family socioeconomics and the practice of providing MPASI (p value= 0.092). Conclusion: Family socio-economics does not have a significant relationship with the practice of providing MPASI